Co-Infection with COVID-19 and Malaria in a Young Man - Mustafa Mahmood Eid (Dubai Medical Journal)
Malaria is an infectious disease caused by Plasmodium protozoa, which can be fatal if not diagnosed and treated promptly. COVID-19 is a newly emerging disease that can affect different body systems; however, the respiratory system is mainly reported. This case describes a 20-year-old man who presented with fever and joint pain and was found to have P. falciparum malaria in addition to a positive SARS-CoV-2 test. The patient improved after he was treated with antimalarial medications in addition to supportive therapy. A co-infection of malaria and COVID-19 can occur. Thus, more studies need to be conducted on this co-infection. Besides, other diagnoses should be highly suspected in patients presenting with symptoms suggestive of SARS-CoV-2 infection, especially in vulnerable patients.